2019
DOI: 10.1097/ico.0000000000001960
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Keratitis in Stevens–Johnson Syndrome: A Prospective Study

Abstract: Purpose: To evaluate the microbiological profile and outcome in cases with infective keratitis in Stevens–Johnson syndrome (SJS). Methods: Eighty-three eyes of 68 patients with SJS presenting with microbial keratitis were recruited and managed with standard antimicrobial therapy. Results: Microbial keratitis developed in 34% of patients with SJS (83 eyes, 68 patients) over a period of 5 years. Four eyes (4.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 8 publications
2
15
2
1
Order By: Relevance
“…The most common bacteria isolated were Staphylococcus species (35% eyes). Sharma et al prospectively studied eyes with microbial keratitis and noted isolated bacterial infections in 63% eyes with polymicrobial infections in 29% eyes (19). Corneal perforation was noted in 31% eyes out of which 70% of eyes required a therapeutic penetrating keratoplasty, thus demonstrating a higher need for surgical interventions in these eyes.…”
Section: Classification Of Chronic Sequelaementioning
confidence: 99%
“…The most common bacteria isolated were Staphylococcus species (35% eyes). Sharma et al prospectively studied eyes with microbial keratitis and noted isolated bacterial infections in 63% eyes with polymicrobial infections in 29% eyes (19). Corneal perforation was noted in 31% eyes out of which 70% of eyes required a therapeutic penetrating keratoplasty, thus demonstrating a higher need for surgical interventions in these eyes.…”
Section: Classification Of Chronic Sequelaementioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Positive rate of bacterial culture from corneal lesions in different regions, References [ 5 , 7 , 8 , 11 , 12 , 16 , 18 , 21 , 28 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%
“…How the ocular surface microbiome and ocular surface immunity interact is yet unknown, but studies have seen the importance of their balance and, therefore, given that SJS patients have generally abnormal ocular surfaces, they are prone to the imbalance that subsequently can induce commensal bacteria to become pathobionts and lead to possible opportunistic infections. [10,19,20,22,23] Previous studies reported that the conjunctival swab culture positivity of SJS patients was observed in 59 -95%. [8, 11, 18] Venugopal et al found that the most common isolate in SJS conjunctiva was Coagulasenegative Staphylococci followed by Corynebacterium species and that only 7.6% was observed to have multiple isolates.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Likewise, a weakened and damaged ocular surface of SJS patients may be more prone to harbor pathobionts and allow opportunistic infections, which can also be aggravated by surgical interventions or medical therapy such as topical immunosuppressant or antibiotics. [19][20][21][22][23] Herein, we investigated the conjunctival microbiota of Korean SJS patients using conventional swab cultures, and identi ed factors associated with the conjunctival culture results.…”
Section: Introductionmentioning
confidence: 99%